Development of Electronic Flight Bag Application for Small Turboprop Aircraft Weight and Balance Calculation - Malik, Rahadian Maulana; Indriyanto, Toto (Warta Penelitian Perhubungan, 2023)
Nowadays, many airlines in modern aviation utilize an Electronic Flight Bag (EFB) during flight to replace traditional paper-based systems. Considering the importance of aircraft weight and balance calculation to flight operations, the flight mission of X-123 (a small turboprop aircraft) and the current EFB market, research on weight and balance application development of X-123 on EFB in Indonesia is conducted. The research aimed to develop the application according to Indonesian regulations and to examine the weight and balance characteristics of X-123 through several simulations in a programming language, Python. Furthermore, Staff Instruction 8900 - 3.3 is analyzed to identify the factors that should be considered in EFB development. The global architecture design and substantial features are, then, proposed as an initial EFB development. In the global architecture design, the utilization of a gateway becomes important as a connection between the EFB developer and the client, providing aircraft data changes flexibility to the client. Moreover, the calculation formula is completely discussed in the calculation modules as a substantial feature and implemented in the simulation. According to simulation results, the payload weight and payload distribution changes can affect significantly the CG location. It is recommended to weigh and assign the payload before flight to ensure flight operation safety. In addition, the proposal of the architecture design and substantial features can be used as a reference and further developed by the Indonesian aviation companies.